Treatment of Pediatric Acute Graft-versus-Host Disease—Lessons from Primary Immunodeficiency? - Flinn, Aisling M.; Gennery, Andrew R. (Frontiers in Immunology, 2017)
Allogeneic hematopoietic hematopoietic stem cell transplant (HSCT) is used to treat increasing numbers of malignant and non-malignant disorders. Despite significant advances in improved HLA-typing techniques, less toxic conditioning regimens and better supportive care, resulting in improved clinical outcomes, acute graft-versus-host disease (aGvHD) continues to be a major obstacle and, although it principally involves the skin, gastrointestinal tract and liver, the thymus is also a primary target. An important aim following HSCT is to achieve complete and durable immunoreconstitution with a diverse T-cell receptor (TCR) repertoire to recognise a broad range of pathogens providing adequate long-term adaptive T-lymphocyte immunity, essential to reduce the risk of infection, disease relapse and secondary malignancies. Reconstitution of adaptive T-lymphocyte immunity is a lengthy and complex process which requires a functioning and structurally intact thymus responsible for the production of new naïve T-lymphocytes with a broad TCR repertoire. Damage to the thymic microenvironment, secondary to aGvHD and the effect of corticosteroid treatment, disturbs normal signalling required for thymocyte development, resulting in impaired T-lymphopoiesis and reduced thymic export. Primary immunodeficiencies, in which failure of central or peripheral tolerance is a major feature, because of intrinsic defects in hematopoietic stem cells leading to abnormal T-lymphocyte development, or defects in thymic stroma, can give insights into critical processes important for recovery from aGvHD. Extracorporeal photopheresis (ECP) is a potential alternative therapy for aGvHD, which acts in an immunomodulatory fashion, through the generation of regulatory T-lymphocytes (Tregs), alteration of cytokine patterns and modulation of dendritic cells (DCs). Promoting normal central and peripheral immune tolerance, with selective down-regulation of immune stimulation, could reduce aGvHD, and enable a reduction in other immunosuppression, facilitating thymic recovery, restoration of normal T-lymphocyte ontogeny, and complete immunoreconstitution with improved clinical outcome as the ability to fight infections improves and risk of secondary malignancy or relapse diminishes.